(untitled) (Journal of Pharmaceutical Negative Results, 2023)
The training of highly qualified specialists in accordance with international standards is largely associated with the sustainable development of professional education and the training of teaching staff. In turn, it is necessary to implement the educational process by creating advanced pedagogical technologies, which makes it necessary to organize the educational process taking into account the requirements of the market economy, introduce appropriate training technologies and constantly improve the content of the educational process. This question is relevant for the development of aesthetic ability, which is an important part of the education of a harmoniously developed personality in the process of training future specialists, studying it from a pedagogical point of view and introducing it to a new qualitative level. The reliability of the research results lies in the fact that the research process was applied various approaches to the studied phenomena, the approach to the analysis of the obtained results to a variety of different paradigms, reveals the validity of the study's analyses and the effectiveness of experimental works on the theoretical and experimental phase, mathematical-statistical methods, provides an introduction to the practice of scientific conclusions, proposals and recommendations, as well as the confirmation of the implementation of the results of the organizations having the appropriate authority. The scientific significance of the research results is determined by the creation of a model for improving the aesthetic ability of future teachers, the scientific and theoretical interpretation of the factors that ensure its effectiveness, the use of technologies proposed to solve the problem, the developed effective methods and tools, and educational guidelines used to improve the efficiency and quality of the educational process in the system of professional education. The practical significance of the research results is expressed in the fact that the results obtained in the course of improving the aesthetic ability of students, the proposed scientific and theoretical conclusions and general pedagogical methodological recommendations serve to improve the educational and methodological support of vocational education institutions.